Analisis Variasi Tegangan dalam Proses Pelapisan Nikel-Krom Material ST37 terhadap Ketebalan dan Kekilapan Permukaan - Octa, Moch. Hersan Maudian; Utama, Firman Yasa; Puspitasari, Dewi; Nugroho, Aji (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The advancement of manufacturing technology has driven the need for innovation in metal surface protection, one of which is through the electroplating method. This process uses electric current to deposit a coating metal onto the surface of a base metal, aiming to improve corrosion resistance, hardness, and surface aesthetics. Electrical voltage is a key parameter that influences the quality of the resulting coating. This study aims to analyze the effect of electrical voltage on the thickness and gloss of electroplated metal coatings. This study employed an experimental approach consisting of a literature review, problem identification, preparation of tools and materials, testing, and data analysis. The main equipment and materials used in this research included ST37 material, a DC power supply with voltage variations of 3 V, 6 V, and 12 V, electrodes, and an electrolyte solution composed of nickel and chromium. Data were obtained by measuring the coating thickness using a Thickness Gauge and surface gloss using a Gloss Meter for each voltage variation. The results of this study indicate that the applied voltage significantly affects the thickness and glossiness of the electroplated coating. The highest values were obtained at 6 V, with an average coating thickness of 20.80 µm and a gloss value of 566 GU, indicating the formation of a smooth and highly reflective surface.